Live donor liver transplantation for type 1 tyrosinemia: An analysis of 15 patients - Karaca, Can A.; Yilmaz, Cahit; Farajov, Rasim; Iakobadze, Zaza; Aydogdu, Sema; Kilic, Murat (Pediatric transplantation, 2019)
Type 1 tyrosinemia is a rare metabolic disorder of the tyrosine degradation pathway. Due to the rarity of the disease, the best evidence literature offers is limited to guidelines based on expert opinions and optimal treatment is still a debate. LT serves as a definitive treatment of the defective metabolic pathway in the liver along with other serious disease manifestations such as LF and HCC. Nitisinone is a relatively new agent that is currently recommended for the medical management of the disease. Its mechanism of action is well understood, and efficacy is well established when started presymptomatically. This study aims to evaluate outcomes of 15 patients with type 1 tyrosinemia who underwent LT in nitisinone era and discuss its effect on prevention of HCC. A LT database of 1037 patients was reviewed. Data from 15 patients with type 1 tyrosinemia were retrospectively analyzed. All the patients except one were treated with nitisinone prior to LT. Most common indications for LT were LF and suspicious nodules. Seven patients had HCC. Mortality rate was 20% (n = 3). Nitisinone treatment has opened new horizons in the management of type 1 tyrosinemia, but LT still remains the only option for the patients developing LF and in the event of HCC. Neonatal screening programs utilizing blood succinyl acetone as the marker should be encouraged especially in the countries, such as Turkey, with high prevalence of consanguineous marriages.